The Effect of Location, Atmosphere, and Service Quality on Customer Satisfaction at Warkop Gelas Batu (GB) 5 Ahmad Yani Rantauprapat - Ruwy Mai Andini; Marlina Siregar; Nurintan Asyiah Siregar (PT Mattawang Mediatama Solution, 2022)
Warkop gelas batu 5 Ahmad Yani Rantauprapat is effort moving business _ in the field culinary that sells miscellaneous food and drink . On research this addressed for knowing variable X1 location, X2 atmosphere , X3 Quality service and satisfaction customer . In study this population used _ that is whole consumers who have visit to warkop gelas batu 5 at least 1 time, and taking sample with formula unknown population as many as 97 respondents . Data collection is carried out with spread questionnaire use googleform and measure with scale likert . Data analysis techniques in research this use PLS (partial least square) analysis which is analysis equality -based Structural Equation Modeling (SEM) variant with use softwear SmartPLS 3. Research results this show that location take effect positive and significant to satisfaction customer . Atmosphere take effect no significant to satisfaction customer and quality service take effect positive and significant to satisfaction customer